Organic and mineral amendments on rice (oryza sativa L.) yield and nutrient recovery efficiency - Perumal, Palanivell (2016)
Highly weathered soils such as Ultisols and Oxisols in Malaysia and elsewhere are low pH and nutrients but they are high in iron (Fe) and aluminium (Al). The high Fe and Al contents of these soils reduce their productivity. As a result, substantial amounts of fertilizers are used to sustain productivity of crops cultivated on Ultisols and Oxisols, especially those in the tropics. However, excessive use of chemical fertilizers degrades the environmental quality. To reverse this undesirable practice, amendments which are high in pH and cation exchange capacity such as crude humic substances, chicken litter biochar, and clinoptilolite zeolite could be exploited to improve soil chemical properties, lowland rice (cv. MR219) growth, nutrients uptake, nutrients recovery efficiency, and yield. River sand and the amendments were mixed at different rates to select the potential rice seeds germination medium. Crude humic substances, chicken litter biochar, and clinoptilolite zeolite at different rates were mixed with soil to determine their effects on ammonia volatilization, nutrients availability, nutrients (N, P, and K) adsorption and desorption capacity, pH buffering capacity, lowland rice growth, nutrients uptake, and nutrients recovery efficiency in laboratory, greenhouse, and field studies. Potential treatments of a greenhouse study were selected and further evaluated in field trials. Application of crude humic substances and chicken litter biochar did not minimize ammonia volatilization whereas, clinoptilolite zeolite reduced ammonia loss from urea under waterlogged condition. However, the three amendments improved soil pH and the availability of Ca, Mg, and Na in Typic Paleudults under laboratory condition. The organic amendments (crude humic substances and chicken litter biochar) increased soil total organic carbon, organic matter content, total N, and availability of K+ and Mn2+. Phosphorus availability was improved upon chicken litter biochar application whereas under laboratory condition, exchangeable ammonium increased with the application of clinoptilolite zeolite. Addition of crude humic substances reduced nutrients adsorption (N, P, and K) and K desorption rate however, they increased N and P desorption rate and pH buffering capacity. Chicken litter biochar increased N adsorption and pH buffering capacity but, it reduced P and K adsorption and so was N and P desorption rate. Lower N desorption rate with high N adsorption of the chicken litter biochar indicates the NH4 +-N fixing capacity of this organic amendment. Clinoptilolite zeolite increased N and K adsorption, N desorption rate, and pH buffering capacity but, it reduced P adsorption and desorption rates of P and K. Higher K adsorption with lower K desorption rate indicates that clinoptilolite zeolite has high affinity for K. Clinoptilolite zeolite (15%) mixed with sand (85%) was selected as germination medium for the greenhouse and field trials as it improved rice seedling shoot elongation. From the greenhouse study, crude humic substances at 5 t ha-1, chicken litter biochar at 15 t ha-1, and clinoptilolite zeolite at 15 t ha-1 were chosen for further field verification due to their potential to improve rice plant growth variables and selected soil chemical properties. Chicken litter biochar at 15 t ha-1 and crude humic substances at 5 t ha-1 increased MR219 rice yield by 88% and 38%, respectively in the first field trial. Reduced rates of crude humic substances (1.67 t ha-1) and chicken litter biochar (5 t ha-1) with reduction of chemical fertilizers by 37% increased rice yield by 57% and 75%, respectively in the second field trial. In the third field trial, the carryover effect of the chicken litter biochar on the rice yield was superior to those of crude humic substances, clinoptilolite zeolite, and the standard fertilization. Regardless of field trial, application of clinoptilolite zeolite had similar effect as normal fertilization on rice yield. Although, the conventional practice was profitable at the initial cycles, the profit associated with this practice decrease to loss by the third cycle. Rice farmers in Malaysia who patronize the conventional method are still surviving because of the Malaysian government subsidies on fertilizers, lime, and seeds. Irrespective of field trial, the use of crude humic substances was economically viable however, farmers can breakeven at second and third field cycles, respectively if they adopt chicken litter biochar and clinoptilolite zeolite in their farming practices. Incorporating crude humic substances or chicken littler biochar in the Malaysian rice cultivation is economically viable compared to the existing practice. It is recommended to produce biochar commercially in Malaysia from the agro industrial organic wastes or transfer technology to farmers to produce their own biochar to reduce the production cost. To refine this study, the organic and mineral amendments can be mixed to improve soil quality and rice yield. Apart from N, P, and K, other nutrients contribution to increase rice yield should be comprehensively studied in future studies.